PEMETAAN DAYA DUKUNG TANAH DIBEBERAPA DAERAH ACEH BESAR MENGGUNAKAN DATA CONE PENETRATION TEST - Devi Sundary; Banta Chairullah; Hendra Gunawan (JURNAL TEKNIK SIPIL, 2014)
Bearing capacity of the soil and the foundation has a close link with the level of safety to the occupants of a building. A foundation design said to be true if the load transmitted by the foundation to the ground does not exceed the power of the land concerned.If the soil strength is exceeded, then a decrease (settlement) excessive or collapse of land will occur, causing damage to the construction which is above the foundation. This research aimsto obtain the value of the soil bearing capacity of shallow foundations in several areas of Aceh Besar, and used as a mapping using ArcGIS 9.2 software. Secondary data used is Cone Penetration Test (CPT) ere obtained from the Laboratory of Soil Mechanics Faculty of Engineering, University of Syiah Kuala. Number of points CPT or sondir is 34 points.  Furthermore, to determine the location of these points in the field using GPS (Global Positioning System). The result shows that most of the area in the study area has a bearing capacity of the land is permitted 50 ton / m2. The area has bearing capacity permits between 50 ton/m2 to 100 ton/m2 occupied area Siem, Cot Gue, Bilui, Adjunct, Baet, Mon Ikeun,Lamkruet, and Lhoknga. Furthermore, the results of the bearing capacity of land used as a mapping so that it becomes a reference in planning the foundation of a building or otherinfrastructure in the region of Aceh Besar.